2D positional mapping of casting condition driven microstructural distribution in organic thin films. (28th November 2019) - Kumari, Nikita; Pandey, Manish; Nagamatsu, Shuichi; Pandey, Shyam S.
Abstract: Fabrication of large-area thin films and their swift characterization is highly desired for the commercial aspects of the organic electronic devices. Although a number of techniques have been proposed for the large-area thin film fabrication, the microstructural variation is still an issue. In this work, the facile characterization of distribution in thickness and macromolecular ordering in the drop-casted and spin-coated poly(3-hexylthiophene) thin films have been performed through newly developed 2D positional mapping technique. Through this technique, a comparative analysis of the absorption spectra in terms of peak absorbance and excitonic bandwidth ( W ) was performed for the whole sample, the lower value of W observed for the drop-casted thin film depicts its molecular ordering. Moreover, the difference in W (≈ 10 meV) was noticed between two points (≈1 mm apart) on the drop-casted film, which corresponds to the difference in microstructural ordering and it is complicated to characterize through the conventional spectroscopic techniques.